A case study of an internationalization process of a private higher education institution in Malaysia - Abu Bakar, Abdul Rahim; Abdul Talib, Asmat Nizam (Gadjah Mada University, 2013)
The increasing competition and commercialization of higher education has led to the internationalization of Higher Education Institutions (HEIs) around the world.While internationalization appears to be inevitable, differences are apparent in its definitions, depth, scope and mode. The main aim of this paper is to assess the internationalization efforts of Malaysian HEIs through a case study on the internationalization process of one private HEI. The case highlights various weaknesses of the internationalization effort in the institution.The symptoms and the causes of the problems in the institution corroborate similar findings in other studies involving the internationalization of HEIs. Suggestions and recommendations are presented to enable other organizations that wish to undertake similar internationalization efforts to learn from the case study institution's experience.